Exploring the therapeutic potential of Moringa oleifera Lam. in Traditional Chinese Medicine: A comprehensive review - Shivendra kumar; Yogesh Murti; Swamita Arora; Wasim Akram; Harsh Bhardwaj; Kapil Gupta; Akshaya Sachdev; Jyoti Devi; Santosh Kumar; Bikash Kumar; Vivek Dwivedi; Shahnawaz Sameem; et al. (Elsevier, 2024)
Introduction: Moringa oleifera Lam. (MOL), sometimes known as the drumstick tree or horseradish tree, has been extensively studied for its pharmacological properties and nutritional benefits. Recently, there has been an increased interest in using this versatile plant in Traditional Chinese Medicine (TCM) procedures. This comprehensive analysis investigates Moringa oleifera's therapeutic potential in TCM, focusing on its traditional usage, phytochemical composition, pharmacological activity, and possible applications in managing various health disorders. Methods: We looked up online databases (PubMed, Web of Science, Google Scholar, Elsevier, ACS, Springer, CNKI) and novels for literature on Moringa oleifera Lam. and its pharmacological activity, using keywords like Moringa oleifera, biological properties of Moringa, and Traditional Chinese Medicine. Results: We address Moringa oleifera's function in TCM formulations, its synergistic effects with other herbal constituents, and its compatibility with TCM principles through a literature review. Furthermore, we look at the problems and potential for bringing Moringa oleifera into TCM practice, such as quality control, standardisation, and cultural adaptation. Discussion: This study emphasises the need for additional research and clinical investigations to fully understand Moringa oleifera's medicinal potential in TCM and allow its integration into modern healthcare systems. However, further research in animal models is needed to determine their efficacy and safety.